CoFI - Consensus on Infant Formulas: The Opinion of Portuguese Experts on Their Composition and Indications - Rêgo, Carla (2018)
Introduction: Breastfeeding has unique health benefits. Exclusive breastfeeding is recommended during the first six months of life and should be maintained during complementary feeding. Alternatively, infant formulas, which are designed to mimic human breastmilk to promote similar metabolic and growth profiles, can be used. This study aimed to assess the opinion of Portuguese paediatricians with expertise in nutrition on the composition, benefits and indications of commercialised infant formulas.Material and Methods: A survey based on the Delphi method with application of a questionnaire developed by a scientific committee was issued to a panel of paediatricians with expertise in nutrition. An initial questionnaire that included 65 items covering 11 areas was administered in two rounds.Results: Twenty-one experts participated, and the final response rate was 87.5%. The panel was in agreement in 68.3% of the enquired items, namely that infant formulas should be used only when breastfeeding is not possible. Notwithstanding, the opinion of the panel was heterogeneous on a number of issues, particularly those related to the advantages and indications of ‘special’ or modified infant formulas (partially hydrolysed formulas and anti-colic, anti-constipation and anti-regurgitation formulas) and of young child formulas (‘growing-up formulas’).Discussion: A wide consensus was recorded on the nutritional quality, food safety and indications attributed to commercialized infant formulas.Conclusion: The opinion of Portuguese experts was consensual in most of the enquired topics. The absence of consensus was mostly related to issues that remain under debate in the literature and lack robust scientific evidence.